Integrating multiple adsorption sites and tortuous diffusion paths into a metal–organic framework for C3H4/C3H6 separation. Issue 44 (30th October 2019) - Wu, Xue-Qian; Xie, Yabo; Liu, Jing-Hao; He, Tao; Zhang, Yong-Zheng; Yu, Jiamei; Kong, Xiang-Jing; Li, Jian-Rong
Abstract : By integrating open metal sites, Lewis basic sites, and tortuous diffusion paths, a new metal–organic framework has been designed and synthesized, which exhibits high adsorption capacity and excellent selectivity for separating a C3 H4 /C3 H6 mixture. Abstract : By integrating open metal sites, Lewis basic sites, and tortuous diffusion paths, a new metal–organic framework has been designed and synthesized, which exhibits high adsorption capacity and excellent selectivity for separating a C3 H4 /C3 H6 mixture. Meanwhile, the molecular packing state, dynamic diffusion coefficient of gases within the framework, and binding interaction are studied by molecular simulations.